Early neuroborreliosis in children, Bannwart syndrome (clinical observations) - K. V. Markova; E. Yu. Skripchenko; N. V. Skripchenko; E. Yu. Gorelik; A. A. Vilnits; A. V. Astapovа; N. F. Pulman (Детские инфекции (Москва))
The problem of ixodic tick-borne borreliosis remains relevant due to its ubiquity, high incidence, especially in the Northwestern Federal District, a variety of clinical manifestations, as well as the possibility of chronization, including in children.Purpose: to describe our own clinical observations of Bannwart syndrome, which developed during the dissemination of the pathogen.Results. Bannwart syndrome is pathognomonic for borreliosis symptoms, including a triad of clinical manifestations: serous meningitis, single- or bilateral lesion of facial nerves, polyneuropathy. Timely clinical and adequate laboratory diagnostics determine the favorable course of the disease.